Regime-dependent output convergence in Latin America - Holmes, Mark (Estudios de Economía, 2016)
This paper tests for long-run output convergence between a sample of eightLatin American countries and over the study period 1900-2003. The keycontribution of this paper is in terms of the econometric methodology wherenon-stationarity of log real per capita income differentials is tested within aMarkov regime-switching framework. In contrast to existing studies, this paperdefines two new concepts of output convergence where one allows for thepossibility that output differentials behaviour either switches between stationaryand non-stationary regimes (partial convergence), or switches between stationaryregimes characterised by differing degrees of persistence (varied convergence).Whereas standard univariate and panel data unit root testing clearly suggestthat output differentials are non-stationary, employment of the regime-switchingmethodology indicates that most of the sample is characterised by the existenceof two distinct stationary regimes. Furthermore, it is argued that the often-citedconvergence rate of two per cent per annum is likely to be an underestimate.